Molekuler Method of Portofolio Resume Assignment to Improving Students Concept Comprehension Towards Molecular Cellular Biology Class - Tomi Hidayat; Nasral Nasral; Santoso Santoso; Pariyanto Pariyanto (Postgraduate, University of Mataram, 2023)
Cell and molecular biology are among the topics that have led to the application of molecular technology. Problems arise when learners lack understanding of concepts or even frequent misconceptions due to many abstract concepts. This study aims to determine the level of student understanding through a resume in the form of a portfolio. The research method used descriptive approach. The population of the study is the students of Biology Education study program which has taken the subject of cell Biology and molecular number of 102 students, and the sample determination using random cluster so that 40 students are obtained. Data were analyzed descriptively-quantitative. Based on the findings in the field, it is known that the average value of the resume portfolio of 71.60 and categorized high. Thus, the students' concept of understanding is in the high category so that the assignment method makes the resume in the form of portfolio able to give better understanding of the concept of lecture material of Cell and Molecular Biology, with the average value of concept understanding through portfolio is in high category